IMPLEMENTASI PROGRAM MANDIRI PANGAN DALAM PENANGGULANGAN KEMISKINAN DI KOTA SEMARANG - Andy Kurniawan; Hartuti Purnaweni; Fathurrohman Fathurrohman (Journal of Public Policy and Management Review, 2015)
One of poverty reduction program in Semarang is independent food program. This program is implemented in village where most society are poor. It began in 2010, and the village that implemented this program are Wates Village in Ngaliyan sub district and Wonolopo Village in Mijen sub district. This research used descriptive qualitative methods. Selection of informants used purposive sampling. Implementation of the program is observed through the implementation model of George C. Edward and Van Meter and Van Horn. The factors that affect the implementation of independent food program are communication, resources, dispotition, standards, and objectives. Based on the result of research, the implementation of the independent food program to reduction poverty in Semarang not going well, because there is deficiency. First, the lack of understanding Mekar 3 goats group cause the goats die. Second, the lack of human resources from Ketahanan Pangan office to control independent food program in Semarang only did by three persons. Third, lumbung pangan group not fully doing by the poor society as the program target. The suggestion that given are: (1) Need to socialize and intensive assistance to each group. (2) Increase employee for Ketahanan Pangan office. (3) Increase commitment and seriousness of Ketahanan Pangan office with food self-group. (4) training routine for the groups.